External Morphology and Internal Oral Features of the Tadpole of Crossodactylus caramaschii (Anura: Hylodidae) - Toscano, Nayara P.; Alecrim De Freitas, Nayara H.; De Rezende, Michelle Robin C.; Provete, Diogo B.; Lyra, Mariana [UNESP]; Haddad, Célio F. B. [UNESP]; Rossa-Feres, Denise De Cerqueira [UNESP]; Da Silva, Fernando R. (Society for the Study of Amphibians and Reptiles, 2019)
We describe the larval external morphology and internal oral features of Crossodactylus caramaschii sampled in protected areas of the Atlantic Forest in southeastern Brazil. The tadpoles of C. caramaschii (Gosner stage 38) have an ovoid body in dorsal view and globular in lateral view, dorsal eyes, a ventral oral disc bordered by a single row of marginal papillae, with a wide gap on the anterior labium, and few and scattered submarginal papillae. The labial tooth row formula is 2(2)/3(1), with A-1 shorter than A-2, and P-3 shorter than P-1 and P-2. This is the first description of the larval morphology of this species and may help future studies on the intrageneric relationships of Crossodactylus.